2015
DOI: 10.1007/s00213-015-4071-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of general anesthetics on anxiety-like behavior in formalin-induced pain: involvement of ERK activation in the anterior cingulate cortex

Abstract: This study suggests that sevoflurane, but not intravenous anesthetics, inhibits pain-related anxiety, along with ERK activation in the ACC, probably through inhibition of spinal nociceptive transmission. Intraoperative application of inhaled anesthetics may be a better choice to reduce postoperative anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Moreover, previous anesthesia with this barbiturate seems not to interfere with the detection of the anxiolytic-like effect of diazepam in the EPM. Corroborating our results, pentobarbital, another barbiturate, also did not produce any change in rat's behavior in the EPM (Luo et al 2015). On the other hand, Torres et al (1996) showed an acute anxiolytic-like effect of a subanesthetic dose of thiopental in rats tested in the one-way-avoidance test.…”
Section: Thiopental Effectssupporting
confidence: 83%
See 2 more Smart Citations
“…Moreover, previous anesthesia with this barbiturate seems not to interfere with the detection of the anxiolytic-like effect of diazepam in the EPM. Corroborating our results, pentobarbital, another barbiturate, also did not produce any change in rat's behavior in the EPM (Luo et al 2015). On the other hand, Torres et al (1996) showed an acute anxiolytic-like effect of a subanesthetic dose of thiopental in rats tested in the one-way-avoidance test.…”
Section: Thiopental Effectssupporting
confidence: 83%
“…We performed the behavioral tests on naive animals, which means that the animals were not exposed to surgical trauma. There are some evidences suggesting that surgical trauma impacts animal's behavior (Li et al 2010;Luo et al 2015;Wang et al 2017).…”
Section: Implications and Limitations Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The anxiolytic and sedative actions of some drugs occur through chloride ion channel opening [12,42,43]. Pentobarbital, an anesthetic drug with actions at GABA A receptors, produces ataxia and motor incoordination [41], but its potency as an anxiolytic agent is equivocal [44,45]. A similar profile was found for oleic acid, which increases the affinity of agonists for the benzodiazepine binding site on GABA A receptors [10].…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, Haseneder et al (28) showed that sevoflurane elevates the expression of the NMDA receptor type 1 and 2B subunits in the hippocampus leading to less anxious behaviour. Another study conducted by Luo et al (29) suggested that sevoflurane inhibits pain-related anxiety, along with ERK activation. However, the relationship between dexamethasone and anxiety is complicated.…”
Section: Discussionmentioning
confidence: 97%